The Effect of Prior Knowledge of English at Elementary School on the Reading Ability of Junior High School Students - Roudhotul Hildayani (JournEEL, 2019)
This research is used quantitative method and the design used in this research was ex post facto. In collecting the data, the reseacher administer questionairre then share the reading test to the students. In analyzing the data, the reseacher used linear regression in SPSS 16.0.the result of this research shows that there is effect or influence between prior knowledge of english and reading ability. Based on the calculation linear reggresion, the gain of sig is 0.021 which is less than 0.05 . it mean s that prior knowledge of english at elementary school influence the reading ability of junior high school students. It can be concluded that the students who get prior knowledge of english at elementary school are having better reading ability than those who do not.